Something old, something bold : bridal showers and bachelorette parties - Montemurro, Beth, 1972- (Rutgers University Press, 2006)
"Contemporary weddings in the United States can be extravagant, highly ritualized, and costly affairs. From the intricate details of the wedding dress, to the painstaking selection of flowers, to the festively-packaged favors offered to guests, they are often the culmination of months of fastidious planning and preparations. In "Something Old, Something Bold", sociologist Beth Montemurro takes a fresh look at the wedding process, offering a perspective not likely to be found in the slew of planning books and magazines readily available to the modern bride. Focusing on two events - bachelorette parties and bridal showers - Montemurro draws upon years of ethnographic research and interviews to explore what these prenuptial events mean to women participants and what they tell us about the complexity and ambiguity of gender roles. The innovation of the bachelorette party - a celebration of the bride-to-be's premarital sexual identity - and the addition of men to the domestically oriented shower have often been thought to indicate gender convergence and a more progressive attitude toward power relations between men and women. But, Montemurro suggests that this is not always the case.; Through these events, the bride-to-be is initiated into the role of wife by her friends and family, who present elaborate and exaggerated scenarios that demonstrate both what she is sacrificing and what she is gaining. Ultimately, Montemurro argues, prenuptial rituals contribute to the stabilization of gender inequalities - that American society at the turn of the twenty-first century is still very much married to tradition and traditional conceptions of masculinity and femininity"--Provided by publisher